1987
DOI: 10.1139/v87-278
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalyzed rearrangement of cyclobutanols. A novel rearrangement

Abstract: E. LEE-RUFF and FRED J. ABLENAS. Can. J. Chern. 65, 1663 (1987). The acid-catalysed dehydration-rearrangement reaction of a-thienyl cyclobutanols 3 and 4 resulted in the formation of tetrahydronaphtho[2,3-blthiophenes 5a and 6 a . The rearrangement to the linearly fused PAH system instead of the expected angularly fused system reflects a-scission of the cyclobutyl ring. A mechanism based on deuterium labelling studies is proposed to account for the product formation. Bicyclic cyclobutanones with an a-aryl subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Dialdehyde ( 12 ) was prepared by palladium-catalyzed Buchwald–Hartwig amination between 2 equiv of 2-(2-bromophenyl)-1,3-dioxolane and 1,4-phenylenediamine. The structures of these reaction products were determined by comparing the spectrum data of these products with those of 2a , 2b , 2c , 2d , 2e , 2f , 2g , 2h , 2i , 5 , 7 , 9 , , and 11 …”
Section: Methodsmentioning
confidence: 99%
“…Dialdehyde ( 12 ) was prepared by palladium-catalyzed Buchwald–Hartwig amination between 2 equiv of 2-(2-bromophenyl)-1,3-dioxolane and 1,4-phenylenediamine. The structures of these reaction products were determined by comparing the spectrum data of these products with those of 2a , 2b , 2c , 2d , 2e , 2f , 2g , 2h , 2i , 5 , 7 , 9 , , and 11 …”
Section: Methodsmentioning
confidence: 99%
“…5 From TAA, thiophene-3-acetyl chloride (TAC) 1 was prepared via reaction with thionyl chloride. 6 ‡ TAC was then reacted with fluoresceinamine, to yield 2. § Polymer 3 was prepared via the electrochemical polymerization on Pt coated glass in MeCN using the method reported for the preparation of poly-TAA.…”
mentioning
confidence: 99%
“…Notes and References † E-mail: m.uttamlal@gcal.ac.uk ‡ Experimental procedure for 1: 6 The reaction of TAA (1.00 g, Acros, 98%) with SOCl 2 (0.8 cm 3 ) at 60 °C for 2 h in dry conditions gave an orangebrown liquid 1 (the excess SOCl 2 was evaporated in vacuo at 35 °C ) with a yield of ca. 80%.…”
mentioning
confidence: 99%
“…Evidence for such an ionic mechanism has been obtained from trapping of the intermediate carbocations with nucleophilic solvents such as water (3) and methanol (4). In our investigations on the preparation of polynuclear aromatic hydrocarbons incorporating thiophene rings (5) we observed that, upon attempted dehydrogenation of the tetrahydro naphthothiophene 1 with DDQ, the only product formed was the unsaturated aldehyde 2. Although oxidations of allylic alcohols with DDQ have been observed (6,7), the conversion of 1 and 2 by DDQ represents formally a demethanation reaction that to our knowledge is unprecedented in quinone chemistry.…”
Section: Introductionmentioning
confidence: 99%